Exploring relationship pathways to prevent intimate partner violence among young women in Malawi - Pereira, Audrey; Chunga, Joseph; Kafumba, Juba; Tsoka, Maxton; Barrington, Clare (Taylor and Francis, 2026)
International estimates of intimate partner violence (IPV) among adolescents and young women are high, indicating the need to address IPV prevention early in life. Structural economic interventions, such as household cash transfer programmes, have the potential to improve the wellbeing of youth who are not the direct recipients of the transfers themselves. However, few studies have addressed this topic in terms of youth romantic and/or sexual relationships. We conducted 39 in-depth interviews with young women aged 19-29 years in households participating in the Government of Malawi’s Social Cash Transfer Programme (SCTP) to examine relationship formation, IPV triggers and experiences, and help-seeking behaviours. We found that young women did not directly attribute SCTP effects to their intimate relationships or IPV experiences. Threats to masculinity and transgressions of women’s gender norms were key triggers of IPV, but specific triggers were linked to specific types of IPV. Furthermore, women sought help for non-IPV concerns more than IPV-related issues. Our results reveal there is a need to strengthen cash transfer programmes and layer them with tailored interventions for adolescents and young women in participant households to improve relationships and prevent IPV early in life.